Optimalisasi Kemampuan Anak Sekolah Dasar Melalui Program Bimbel Matematika Dan Bahasa Inggris di RT 18 RW 02 Pematang Gubernur - S, David Ajun; Septi, Septi; Sahdiya, Beti; Nirmalawati, Nirmalawati; Fadila, Mawar; Kresnawati, Kresnawati; Wahyudi, Yusuf; Susanti, Neri (Universitas Dehasen Bengkulu, 2025)
The Thematic Community Service Program (KKN-T) is a community service initiative carried out by students of Universitas Dehasen Bengkulu during the 3rd Period of 2025, located in Pematang Gubernur Subdistrict, Muara Bangkahulu District, Bengkulu City. This KKN-T program involved 15 groups of students assigned across various neighborhood units (RT) within the area. Our group, assigned to RT 18 RW 02, designed and implemented a tutoring program (bimbel) for elementary school children focusing on two subjects: mathematics and English. This program was developed based on initial observations which revealed that most children had difficulties in understanding basic arithmetic operations (addition, subtraction, multiplication, and division) as well as challenges in memorizing and using basic English vocabulary. The main contributing factors to these problems included the lack of learning assistance at home, limited learning time at school, and the absence of engaging learning methods. To address these issues, we conducted tutoring sessions twice a week using fun and interactive methods such as quizzes, ice breaking activities, and individual exercises. The results of the program showed that the children experienced improvement in their interest in learning, comprehension of the material, and confidence in facing mathematics and English lessons. This program demonstrated that an interactive and enjoyable learning approach can create a positive learning environment and significantly contribute to improving the quality of education in the community. In addition to having a positive impact on the students, this activity also served as a means for students to actualize themselves by applying the knowledge and skills they have acquired in university to real life situations.